2006
DOI: 10.1074/jbc.m600544200
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Perineuronal Net Extracellular Matrix in Rat Brain

Abstract: We developed a method to extract differentially chondroitin sulfate proteoglycans (CSPGs) that are diffusely present in the central nervous system (CNS) matrix and CSPGs that are present in the condensed matrix of perineuronal nets (PNNs). Adult rat brain was sequentially extracted with Tris-buffered saline (TBS), TBS-containing detergent, 1 M NaCl, and 6 M urea. Extracting tissue sections with these buffers showed that the diffuse and membrane-bound CSPGs were extracted in the first three buffers, but PNN-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
147
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 315 publications
(154 citation statements)
references
References 85 publications
6
147
0
1
Order By: Relevance
“…The NG2 ectodomain of 290 kD can be extracted with PBS from the ECM of the rodent brain (Figures 3B and S1) [31],[32]. To analyze the effect of activity-dependent effects of the whole neural network on NG2 cleavage within OPC, we subjected acute hippocampal slices to cLTP (PFR incubation) or incubation with 4AP + BCC and analyzed levels of the released NG2 ectodomain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NG2 ectodomain of 290 kD can be extracted with PBS from the ECM of the rodent brain (Figures 3B and S1) [31],[32]. To analyze the effect of activity-dependent effects of the whole neural network on NG2 cleavage within OPC, we subjected acute hippocampal slices to cLTP (PFR incubation) or incubation with 4AP + BCC and analyzed levels of the released NG2 ectodomain.…”
Section: Resultsmentioning
confidence: 99%
“…Acute rat hippocampal slices [84] were incubated for 15 min with PFR or 4AP + BCC and subsequently transferred to standard artificial cerebrospinal fluid (aCSF) without Mg 2+ and protease inhibitors, followed by tissue digestion with chondroitinase ABC [32] and Western Blot analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies indicated that adult brain as well as immature brain is enriched with extracellular matrix components [82]. Unlike the extracellular matrices of other tissues, those of the brain lack collagen fibers, and are composed mainly of proteoglycans, tenascins and hyaluronic acid.…”
Section: Future Directionsmentioning
confidence: 99%
“…The CSPG binding may convert Sema5A from an attractive to an inhibitory guidance cue (Kantor et al, 2004). Sema3A, a repulsive guidance molecule, may interact with CS-E enriched in the PNNs and this interaction could mediate the repulsive function of Sema3A (De Wit et al, 2005; Deepa et al, 2006; Kwok et al, 2011). In addition, the GAGs of CSPGs may bind to extracellular calcium or its channels and regulate neuronal growth by affecting calcium availability and entry into neurons (Hrabetova et al, 2009).…”
Section: Traditional Notion Of Axon Growth Suppression By Cspgsmentioning
confidence: 99%